The Aboriginal Australian Family Wellbeing Program: A Historical Analysis of the Conditions That Enabled Its Spread - McCalman, Janya; Bainbridge, Roxanne; Brown, Catherine; Tsey, Komla; Clarke, Adele (Frontiers in Public Health, 2018)
Introduction: Spreading proven or promising Aboriginal health programs and implementing them in new settings can make cost-effective contributions to a range of Aboriginal Australian development, health and wellbeing, and educational outcomes. Studies have theorised the implementation of Aboriginal health programs but have not focussed explicitly on the conditions that influenced their spread. This study examined the broader political, institutional, social and economic conditions that influenced negotiations to transfer, implement, adapt and sustain one Aboriginal empowerment program - the Family Wellbeing (FWB) program - to at least 60 geographical sites across Australia over 24 years. Material and Methods: A historical account of the spread of the FWB Program was constructed using situational analysis, a theory-methods package derived from a post-structural interpretation of grounded theory methods. Data were collected from published empirical papers, evaluation reports and project papers, and interviews with 18 key actors in the spread of FWB. Social worlds and arenas maps were used to determine the organisations and their representative agents who were involved in FWB spread, and to analyse the enabling and constraining conditions. Results: The program was transferred through three interwoven social arenas: employment and community development; training and capacity development; and social and emotional wellbeing promotion and empowerment research. Program spread was fostered by three primary conditions: government policies and the availability and Aboriginal control of funding and support; Aboriginal leadership, associated informal networks and capability; and research evidence that built credibility for the program. Discussion and conclusion: The continued demand-driven transfer of empowerment programs requires policies that enable Aboriginal control of funding and Aboriginal leadership and networks. Flexible and sustained coordination of program delivery is best leveraged through regional innovation hubs that can work with partner organisations to tailor the program to local end-user needs. Associated research is also needed to evaluate, continually improve program quality, and build program credibility through evidence.